Edukasi dan Implementasi Terapi Kompres Hangat dengan Aromaterapi Lavender Essential Oil untuk Menurunkan Skala Nyeri pada Pasien Post Sectio Caesarea - Niken Dewi Pangestu; Septian Mixrova Sebayang; Ema Wahyu Ningrum (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Post-cesarean section patients often experience severe pain that can hinder the recovery process and interfere with infant care. At Ajibarang Regional Public Hospital, particularly in the Nuri ward, the implementation of non-pharmacological pain management remains limited. Until now, patients have not received interventions such as warm compress therapy combined with lavender aromatherapy. This community service activity aimed to provide health education and implement interventions to improve patient knowledge and reduce pain levels after cesarean section surgery. The methods used included delivering educational materials and carrying out the intervention directly. Pocketbooks were used for education, while hot water bags and diffusers were used for therapy. The results showed that out of 30 participants, 21 (70.0%) had good knowledge before the education, increasing to 24 (80.0%) afterward. Before the intervention, 22 participants (73.3%) reported moderate pain, which decreased to mild pain in 20 participants (66.7%) after the intervention. These findings suggest that education and the application of warm compress therapy with lavender aromatherapy effectively improve knowledge and reduce pain in post-cesarean patients.